Polymorphic analysis of interleukin IL-1β in patients with a diagnosis of Helicobacter pylori in Tabasco, Mexico - Fuentes-Márquez, Liliam A. (2020)
Introduction. Studies on the infection of Helicobacter pylori and the IL-1B gene play an important role within inflammation and its proinflammatory properties that promote defense against pathogens. Polymorphisms have been related to a higher production of IL-1β associated with hypochlorhydria and cancer development under H. pylori infection, so the objective of this study was to evaluate polymorphism in the +3954 region (IL- 1B C> T) of the interleukin IL1β gene. Method. the blood samples were donated and collected to be processed for the determination of H. pylori, by means of the Urease Test (Proindusquim), in the city of Villahermosa Tabasco, Mexico, separating positive and negative samples (control), the positive samples were analyzed by PCR and enzymatic digestion for polymorphic analysis in the +3954 region (IL-1B C> T). Results. 245 samples 78 cases of H. pylori infection were analyzed, 49 were men (62.8%) and 29 women (37.17%), with a mean age of 58.5 years (21-77 years). Genotypic and allelic frequencies observed, 45 individuals were normal homozygotes (CC), 12 rare homozygotes (TT) and 21 heterozygotes (CT), in the control group it was found that 74 individuals were normal homozygotes (CC), 32 were rare homozygotes (TT) and 61 were heterozygous (CT). Conclusion. This study shows an association between the IL-1β + 3954 (C> T) interleukin polymorphism and the predisposition of the population carrying the homozygous CC genotype infected with H. pylori to develop cancer.